2022
DOI: 10.3390/nano12234126
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Switching Kinetics in Thin Ferroelectric HZO Films

Abstract: Ferroelectric polycrystalline HfO2 thin films are the most promising material for the implementation of novel non-volatile ferroelectric memories because of their attractive properties, such as compatibility with modern Si technology, perfect scalability, low power consumption and high endurance. However, for the commercialization of ferroelectric memory, some crucial aspects of its operation should be addressed, including the polarization switching mechanism that determines the switching speed. Although sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Full dependence of the switched polarization on log t set is similar to the arctan function (solid lines in Figure 2b). Previously, it has been shown in HZO film fitting that parameter Γ is much larger than for perovskite ferroelectrics, while the flat area of time distribution is short [21]. This observation is valid for studied structures of both types.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Full dependence of the switched polarization on log t set is similar to the arctan function (solid lines in Figure 2b). Previously, it has been shown in HZO film fitting that parameter Γ is much larger than for perovskite ferroelectrics, while the flat area of time distribution is short [21]. This observation is valid for studied structures of both types.…”
Section: Resultsmentioning
confidence: 57%
“…For other ferroelectric polycrystalline films, it has been shown that the grain pattern (e.g., grain size and orientation) and grain boundaries affect the polarization switching or domain evolution dynamics in ferroelectric nanofilms [19,20]. Furthermore, the depolarization field of spontaneous polarization, an intrinsic feature of ferroelectrics, has been reported to be the cause of the slowing down of polarization switching [21,22]. Interestingly, the influence of the depolarization field differs for hafnium oxide and perovskites [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation